2001
DOI: 10.1177/00131610121969460
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Leadership Style on Teacher Job Satisfaction

Abstract: The article examines the effects of principals’ leadership style (transformational or transactional), principals’ decision-making strategy (autocratic versus participative), and teachers’occupation perceptions on teacher satisfaction from the job. More specifically, it attempts to find out how much of the variation in teachers’job satisfaction can be attributed to their perceptions of their occupation, as compared to their perceptions about their principals’ leadership style and decision-making strategy. A qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
331
1
65

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 423 publications
(429 citation statements)
references
References 34 publications
32
331
1
65
Order By: Relevance
“…Studies revealed that principals' leadership style employed by school directors had a profound impact on teachers' job satisfaction and school effectiveness and therefore, on the quality of education (Bogler, 2001). The leadership behaviours of enhancing high spirits among teachers, consulting teachers on important issues before going ahead, treating teacher as equals and putting teachers' suggestion into effect in the consideration dimension are foretelling of teachers' job satisfaction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies revealed that principals' leadership style employed by school directors had a profound impact on teachers' job satisfaction and school effectiveness and therefore, on the quality of education (Bogler, 2001). The leadership behaviours of enhancing high spirits among teachers, consulting teachers on important issues before going ahead, treating teacher as equals and putting teachers' suggestion into effect in the consideration dimension are foretelling of teachers' job satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies supported the effect of principal's leadership behaviours on teachers' job satisfaction (Dinham & Scott, 1998;Bogler, 2001;Griffith, 2004;Nguni et al, 2006;Cerit, 2009). Studies proved that the principal's leadership behaviour is one of the positive factors that have a direct correlation with teachers' job satisfaction (Bogler, 2001).…”
Section: Principal Leadership Behaviour and Teacher Job Satisfactionmentioning
confidence: 87%
See 2 more Smart Citations
“…After 1999, studies have been based on the examination of relationship between transformational leadership and numerous variables and showed that this style has positive impact on: satisfaction (Griffith, 2004;Leithwood & Jantzi, 2008;Bolger, 2001) motivation (Griffith, 2004;Kruger, Witziers & Sleegers, 2007), commitment (Geijsel, et. al., 2003;Yu, et.…”
Section: Researches Of Transformational School Leadershipmentioning
confidence: 99%